(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the head of the group can choose the type of work that is suitable for his group, taking into account the age characteristics of the members of the group, their opportunities and interests, and the real possibilities of the school.